FRI0163 Smoking Status Does not Seem to Affect Tocilizumab Efficacy in RA Patients. (9th June 2015) - Theander, E.; Proven, A.; Fallang, A.; Svelander, L.; Trollmo, T.
Abstract : Background: Smoking has been shown to affect the response to treatment in RA patients receiving MTX or anti-TNF. To our knowledge no data have been published on the effect of smoking in RA patients treated with tocilizumab. Objectives: To compare clinical efficacy and safety of tocilizumab in RA patients who are current, previous or never smokers. Methods: A non-interventional prospective multi-center study design with the possibility of 6 months retrospective inclusion was chosen in order to reflect clinical practice in 9 clinics in Norway and 20 clinics in Sweden. Depending on local routines, evaluation time points were baseline (first day of tocilizumab treatment) 3, 6 and/or 12 months. Inclusion criteria were diagnosis of RA, as defined by fulfilling at least four of seven American College of Rheumatology (ACR) criteria, informed consent, and no previous treatment with tocilizumab. Exclusion criterion was participation in intervention studies. Results: In total 196 of the planned 200 patients were included between 2010 and 2012. The frequency of smokers was 21%, never-smokers 32%, and former smokers 47%. The smokers had on average smoked 35 (±13) years with a median of 20 pack-years (range 1-55), the former smokers 20 (±13) years with a median of 12 pack-years (range 0-40). Of the former smokers 62% had stopped smoking more than 10 years before study start. Age, sex, disease duration, and presence of anti-CCP antibodies were similar between the 3 groups. Concomitant DMARD use at inclusion was more frequent among smokers (see table ), but only 57% received MTX as DMARD in contrast to 87% of the non-smokers. The frequency of patients receiving tocilizumab as first biologic was highest among smokers; the frequency of patients receiving tocilizumab in monotherapy was highest in never-smokers (see table ). DAS28 disease-activity at inclusion was similar between the 3 groups, see table . At 6 months the disease activity had decreased significantly in all 3 groups, with no significant differences between the groups. On average, DAS28 values were present for 84% of the patients at the 6 months visit. Regression analyses did not indicate any relationships between change in DAS28 from baseline to 6 months and the potential influencing factors: age, sex, disease duration, combination therapy with DMARD or tocilizumab monotherapy and number of previous biologic therapies when comparing non-smokers with smokers and non-smokers with former smokers (p-values between 0.10 and 0.98). There was a tendency for current smokers to report more AEs compared to former and never smokers. Conclusions: The data from this observational study indicate that smokers and non –smokers respond equally well to tocilizumab treatment, in contrast to available evidence from TNF and MTX studies. Age, sex, disease duration, concomitant DMARD use, and previous biologic treatment did not influence the efficacy of tocilizumab treatment over 6 months in the 3 groups observed. Disclosure of Interest: None declared